Body weight dissatisfaction and communication with parents among adolescents in 24 countries: international cross-sectional survey - Abdeen Ziad; Aasvee Katrin; Nansel Tonja; Elgar Frank J; Vereecken Carine A; Al Sabbah Haleama; Ojala Kristiina; Ahluwalia Namanjeet; Maes Lea (BMC, 2009)
Abstract Background Parents have significant influence on behaviors and perceptions surrounding eating, body image and weight in adolescents. The aim of this study was to examine the prevalence of body weight dissatisfaction, difficulty in communication with the parents and the relationship between communication with parents and adolescents' dissatisfaction with their body weight (dieting or perceived need to diet). Methods Survey data were collected from adolescents in 24 countries and regions in Europe, Canada, and the USA who participated in the cross-sectional 2001/2002 Health Behaviour of School-Aged Children (HBSC) study. The association between communication with parents and body weight dissatisfaction was examined using binary logistic regression analysis. Results Body weight dissatisfaction was highly prevalent and more common among girls than boys, among overweight than non-overweight, and among older adolescents than younger adolescents. Difficulty in talking to father was more common than difficulty in talking to mother in all countries and it was greater among girls than among boys and increased with age. Difficulties in talking to father were associated with weight dissatisfaction among both boys and girls in most countries. Difficulties in talking to mother were rarely associated with body weight dissatisfaction among boys while among girls this association was found in most countries. Conclusion The findings suggest that enhanced parent communication might contribute in most countries to less body dissatisfaction in girls and better communication with the father can help avoiding body weight dissatisfaction in boys. Professionals working with adolescents and their families should help adolescents to have a healthy weight and positive body image and promote effective parent - adolescent communication.